Implementasi Sistem Informasi Pengolahan Data Alumni Membantu Akreditas dan Bursa Kerja Metode Content Based Filtering - Yanti, Fitri Rahma; Yahfizham, Yahfizham (Journal of Information System Research (JOSH), 2024)
The author created an information system for alumni data and the job market at SMKN 1 Kutacane because alumni data has not been completely organized and the data available in the files only presents graduate data and diploma proposal data. There is another problem with the running system, namely that the school has difficulty tracking identity. career alumni who have worked, married, or continued their education, as well as schools have difficulty providing or recommending job vacancy information on the job market, because alumni data is not yet available at the school, and they still use manuals via WhatsApp groups. Therefore, the author created a system information on alumni data and special job markets with recommendations using web-based content based filtering methods. The content based filtering method can be used to suggest job vacancy information that matches the profile of the user or job seeker. user or job seeker profile so that it can simplify the process of searching for information. A special job market application is used to recommend appropriate job vacancy information for student alumni. This system can make it easier for teachers to obtain alumni data and can help with accreditation with alumni data.